Innovative Materials Made by Adding Cellulose Ethers to Cement Mortars. (2015) - Jumate, Elena; Manea, Daniela Lucia; Aciu, Claudiu; Molnar, Luminita; Fechete, Radu
Abstract: The present paper has represented a piece of fundamental research, through the complexity and complementary research methods used; the paper brings arguments concerning the evolution in time of the physical and mechanical properties of the mortars, based on complex methods typical of civil engineering and physics. The research is motivated by the need to identify the manner in which cement-based polymer mortar composition can be improved so that they better respond to building requirements. The main objective of the paper lies in showing the effect of cellulose ether in plaster mortars made with Portland cement. The research took place with modern methods and it underlines the contribution of cellulose ethers to increasing the mortar physical and mechanical performance. By optimising traditional formulae, mortars with higher level physical and mechanical properties were obtained.